Results of voluntary cardiovascular examination of elite athletes in Denmark: Proposal for Nordic collaboration - Tischer, S. G.; Mattsson, N.; Storgaard, M.; Høfsten, D. E.; Høst, N. B.; Andersen, L. J.; Prescott, E.; Rasmusen, H. K. (Scandinavian Journal of Medicine & Science in Sports, 2016)
We investigated the cardiovascular status of elite athletes in Denmark, the extent of abnormal cardiac findings - both training related and pathologic - and how participating in cardiac examination was perceived by the athletes. A standardized protocol of questionnaires, physical examination, resting electrocardiogram, and 2D echocardiography was used. In total 1347 elite athletes were invited; 516 athletes (38%) from 30 different sports participated. Results were stored in a web-based database for future research and long-term follow-up. Cardiac pathology was infrequent; eight athletes (1.6%) received a cardiac diagnosis; one athlete (0.2%) diagnosed with long QT syndrome was advised against competition level sports. In total, 60 athletes (11.6%) were referred for additional testing. The athletes presented a very low level of psychological stress before and a slight decrease immediately after the examination as measured by the REST-Q 76 Sport questionnaire. Athletes needing further examinations did not present a higher level of stress after the initial examination compared with athletes with normal test results. Overall, very few athletes were diagnosed with a cardiac condition that increased risk of sudden cardiac death. Less than half of the invited athletes volunteered, but participation was not perceived stressful by the enrolled athletes, not even when additional testing was needed.